DNA damage signaling in the cellular responses to mustard vesicants. (15th June 2020) - Jan, Yi-Hua; Heck, Diane E.; Laskin, Debra L.; Laskin, Jeffrey D.
Highlights: Mustard vesicants such as sulfur mustard and nitrogen mustard are highly reactive with DNA. Mustards can form monofunctional and bifunctional adducts. Cells initiate a DNA damage response to protect against genotoxicity from mustards. The DNA damage response activates signaling cascades important in DNA repair. Inaccurate DNA repair can lead to single and double strand DNA breaks that contribute to cytotoxicity. Abstract: Mustard vesicants, including sulfur mustard (2, 2′-dichlorodiethyl sulfide, SM) and nitrogen mustard (bis(2-chloroethyl)methylamine, HN2) are cytotoxic blistering agents synthesized for chemical warfare. Because they contain highly reactive electrophilic chloroethyl side chains, they readily react with cellular macromolecules like DNA forming monofunctional and bifunctional adducts. By targeting DNA, mustards can compromise genomic integrity, disrupt the cell cycle, and cause mutations and cytotoxicity. To protect against genotoxicity following exposure to mustards, cells initiate a DNA damage response (DDR). This involves activation of signaling cascades including ATM (ataxia telangiectasia mutated), ATR (ataxia telangiectasia and Rad3-related) and DNA-PKcs (DNA-dependent protein kinase, catalytic unit). Signaling induced by the DDR leads to the recruitment and activation of repair related proteins such as phospho H2AX and phospho p53 to sites of DNA lesions. Excessive DNA modifications by mustards can overwhelm DNA repair leading to single and double strand DNA breaks, cytotoxicity and tissue damage, sometimes leading to cancer. Herein we summarize DDR signaling pathways induced by SM, HN2 and the half mustard, 2-chloroethyl ethyl sulfide (CEES). At the present time, little is known about how mustard-induced DNA damage leads to the activation of DDR signaling. A better understanding of mechanisms by which mustard vesicants induce the DDR may lead to the development of countermeasures effective in mitigating tissue injury.